Short-term effects of on-field combined core strength and small-sided games training on physical performance in young soccer players - Arslan, E.; Soylu, Y.; Clemente, F.; Hazir, T.; Kin Isler, A.; Kilit, B. (Biology of Sport, 2021)
This study aimed to compare the effects of 6-weeks combined core strength and small-sided games training (SSGcore) vs. small-sided games (SSG) training on the physical performance of young soccer players. Thirty-eight amateur soccer players (age: 16.50 ± 0.51 years) were randomly assigned to either a SSGcore (n = 20) or a SSG group (n = 18). The SSGcore group performed upper and lower body core strength exercises combined with SSG including 2-, 3- and 4-a-sided soccer games third a week. The SSG group performed only the SSG periodization. Baseline and after the 6-week training period the Yo-Yo Intermittent Recovery Test level 1 (YYIRTL-1), 5-20-m sprint test, countermovement jump (CMJ), squat jump (SJ), triple-hop distance (THD), zigzag agility with ball (ZAWB) and without ball (ZAWOB), three corner run test (TCRT) and Y-balance test. The SSGcore group demonstrated meaningful improvements in 20 m sprint time (SSGcore: -9.1%, d = 1.42; SSG: -4.4%, d = 0.76), CMJ (SSGcore: 11.4%, d = 2.67; SSG: -7.7%, d = 1.43), SJ (SSGcore: 12.0%, d = 2.14; SSG: 5.7%, d = 1.28), THD (SSGcore: 5.0%, d = 1.39; SSG: 2.7%, d = 0.52) and TCRT (SSGcore: -3.7%, d = 0.69; SSG: -1.9%, d = 0.38). Furthermore, the SSGcore group demonstrated meaningfully higher improvement responses in both leg balance score (d = ranging from 2.11 to 2.75) compared with SSG group. These results suggest that the inclusion of core strength training to a SSG periodization is greatly effective to improve speed and strength-based conditioning in young soccer players.